HUBUNGAN KEPADATAN KENDARAAN DENGAN GAS KARBON MONOKSIDA UDARA AMBIEN DAN KARBOKSIHEMOGLOBIN JURU PARKIR DI JALAN GAJAH MADA DENPASAR - BULDA MAHAYANA, I M; BUDIARSA SUYASA, I W; LAKSMIWATI, I D A ALIT (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 1, 2012)
Gajah Mada street is the main road in Denpasar to access traditional market in Badung and Kumbasari Market. It is crowded street with many vehicles pass through it. As a result, this could increase the level of emission gas such as ambient monoxide carbon gas which could affect the concentration of carboxyhemoglobin, exposure time and subjective complaints of sample. his was a cross sectional study of 12 parking man. Data was mainly collected from measurements including the density of vehicles, vehicles type, oil fuel type, vehicle age, ambient monoxide carbon gas, carboxyhaemoglobin, exposure time and subjective complaints of sample. The study found that the average of vehicle density mean per day was 91.338 unit or 3.805,8 unit per hour (very high). The biggest type of vehicle percentage was motorbike 81%, followed by vehicles using premium fuel 93,7%. The age of vehicles below 10 years was 55%. The mean of monoxide carbon gases concentration was 585,96 ?g/m³ per day (mean). The mean of weather situation including humidity was 82,7%, temperature 27,6ºC, eastward wind direction, fair cloudy an wind speed about 1,76 m/second. The average of carboxyhaemoglobin concentration in 12 parking man was 3.8% (very low). The mean of exposure time was 125 minutes. It was noted that there were 9 samples (75%) with complaints and 3 samples (25%) without any complaints. The study concluded that the highest numbers or vehicle density it is very high categories. Monoxide carbon gas concentration it is mean categories and was under threshold limit value. The highest numbers or vehicle density and Monoxide carbon gas concentration between 14.00-16.00 pm and. There was a significant correlation between vehicle density and ambient monoxide carbon gas. The measurement of carboxyhaemoglobin concentration it is very low categories. It also found that the exposure time correlated with the level carboxyhaemoglobin of parking man significantly. It is suggested that the Government of Denpasar City should implement free parking area particularly in crowded traffic time, develop city garden and propose the community to use low fuel emission for vehicles.
Keywords: vehicle density, monoxide carbon gas, carboxyhaemoglobin.